The Role of Technopreneurship Literacy and Entrepreneurship Education in Fostering Entrepreneurial Interest Through Self-Efficacy - Hajar Dewantara; Andi Anggi Kemalasari (Universitas Negeri Makassar, 2024)
This study explores the impact of entrepreneurship education and technopreneurship literacy on fostering entrepreneurial interest among vocational high school students, with self-efficacy serving as a mediating factor. The research adopts a quantitative approach, utilizing data collected through documentation and questionnaires. Path analysis, conducted using SPSS software, reveals that both entrepreneurship education and technopreneurship literacy have a positive and significant influence on students' entrepreneurial interest, both directly and indirectly through the enhancement of self-efficacy. The findings underscore the critical importance of integrating entrepreneurship education and technopreneurship literacy into the curriculum for all departments in vocational high schools. These educational elements not only boost students' self-efficacy but also play a vital role in cultivating a strong interest in entrepreneurship. By fostering these skills and mindsets, vocational schools can better prepare students for entrepreneurial endeavors, contributing to their overall career readiness and potential for success in the business world.